A=B , A-B=B-B , A-B =0 B=C , B-B=C-B, 0=C-B So A-B=0 but also C-B=0 A-B=C-B ...add +b ...A-B+B=C-B+B , A=C
A=0 b=0 c=0
Two: one is 0, the other is -b/a ax2 + bx + c = 0, but c = 0 ⇒ ax2 + bx + 0 = 0 ⇒ ax2 + bx = 0 ⇒ x(ax + b) = 0 ⇒ x = 0 or (ax + b) = 0 ⇒ x = -b/a
Here is one explanation. Suppose A and B are two positive numbers.-A*0 = 0(B-B) = 0, so substitutong this value in place of 0 gives: -A*(B-B) = 0expanding the bracket, -A*B -A*(-B) = 0Adding A*B to both sides, A*B - A*B = -A*(-B) = A*BBut A*B - A*B = 0, which leave -A*(-B) = A*B
a < b → a - a < b - a → 0 < b - a → 0 - b < b - a - b → -b < -a → if a < b then -b < -a which can also be expressed as -a > -b
it cant b done,but u can boil it in a vacume even at 0.c before it solidifies
int gcd (int a, int b) { if (a<0) a= -a; if (b<0) b= -b; while (a!=0 && b!=0 && a!=1 && b!=1) { int tmp; if (a>b) tmp= b, b= a, a= tmp; a= a%b; } if (a==0) return b; else if (b==0) return a; else return 1; }
A*(B-B) = A*0 = 0 Expanding the left hand side, using the distributive property, A*B + A*(-B) = 0 That is, A*B and A*(-B) are additive inverses. Next, (A-A)*(-B) = 0*(-B) = 0 Expanding, A*(-B) + (-A)*(-B) = 0 Therefore A*(-B) and (-A)*(-B) are additive inverses But, from above, the additive inverse of -A*B is A*B Therefore (-A)*(-B) = A*B It is not known when this was proven.
Yes. If a x b = 0 then either a = 0, b = 0, or a = b = 0.
Real numbers are commutative under addition (and subtraction) so a + b - a = a - a + b The set of Real numbers includes an additive identity, 0, such that a - a = 0 so a - a + b = 0 + b The additive identity also has the property that 0 + b = b [= b + 0] so 0 + b = b
A=B , A-B=B-B , A-B =0 B=C , B-B=C-B, 0=C-B So A-B=0 but also C-B=0 A-B=C-B ...add +b ...A-B+B=C-B+B , A=C
Presumably you mean is it true that: ( A nor B ) nor C == A nor ( B nor C ) ? No. Let's make a table: A B C (A nor B) (B nor C) [ (A nor B ) nor C ] [ A nor ( B nor C ) ] 0 0 0 1 1 0 0 0 0 1 1 0 0 1 .... So you see right away for A=0, B=0, and C=1 it doesn't work.
A+A*b does not mean A plus Ab the operation signified by "+" is called "or" the operation signified by "*" is called "and" there are four possible outcomes of a+a*b if a=1 and b=1 the result is 1 if a=1 and b=0 the result is 1 if a=0 and b=1 the result is 0 if a=0 and b=0 the result is 0 a+a*b is 1 if a is 1 and a+a*b is 0 if a is 0 regardless of the value of b thus a+a*b=a Q.E.D.
3b2 + b - 10 = 0 This quadratic equation can be factored. (3b -5)(b +2) = 0 The equation can be solved when either (3b - 5) = 0, or (b + 2) = 0. If 3b - 5 = 0 then 3b = 5 : b = 5/3 If b + 2 = 0 then b = -2 The roots or solutions to this equation are b = 5/3 and b = -2
A=0 b=0 c=0
Yes. AND operation = f(A,B) = AB = A'f(0,B) + Af(1,B) = A'(0B) + A(1B) = A'0 + AB OR operation - f(A,B) = A+B = A'f(0,B) + Af(1,B) = A'(0+B) + A(1+B) = A'B + A1 NOT operation - f(A) = A' = A'f(0) + Af(1) = A'(1) + A(0)
Suppose you have two decimal numbers, A and B. If A - B > 0 then A is the bigger decimal, if A - B < 0 then B is the bigger decimal and if A - B = 0, neither is bigger.